Tabaco y medios de comunicación escritos en España: una atracción fatal Tobacco advertising and printed mass media in Spain: a fatal attraction - Julio Montes; María L. Álvarez (Elsevier, 2006)
Objetivo: La publicidad del tabaco es un poderoso estímulo para iniciar su consumo. Se analizó dicha publicidad en medios escritos en España durante el período 2002-2005. Métodos: Estudio transversal anual de anuncios insertados en los 41 medios escritos de mayor difusión (cerca de 10 millones de lectores). Resultados: En dicho período un 37% de medios insertaron publicidad sobre el tabaco (lectores medios, 4,35 millones). Sólo un 4% de los medios incluyeron campañas antidroga (lectores medios, 0,27 millones). La publicidad del tabaco se incrementó tanto globalmente (del 2,0 al 4,7%) como en medios que la consintieron (del 4,3 al 8,0%). Ello significa que 4 de cada 10 lectores totales y 1 de cada 8 españoles > 15 años recibieron tal impacto publicitario. En el 56% de los anuncios se incluyeron jóvenes. Conclusiones: La publicidad del tabaco es alta en los medios escritos y está dirigida preferentemente a jóvenes. Objective: Tobacco advertising is a powerful factor in encouraging smoking initiation. We analyzed tobacco advertising in written mass media in Spain between 2002 and 2005. Methods: We performed an annual cross-sectional study of advertisements in the 41 most widely disseminated written mass media (nearly 10 million readers). Results: In the period studied, 37% of the media included tobacco advertising (an average of 4.35 million readers). Only 4% of the media included anti-drug campaigns (an average of 0.27 million readers). Tobacco advertising increased from 2.0 to 4.7% (overall) and from 4.3 to 8.0% (in media allowing tobacco advertising). Four out of every 10 readers and one out of eight Spaniards aged 15 years or older were exposed to tobacco advertising. Fifty-six percent of advertisements included young people. Conclusions: Tobacco advertising remains prominent in written mass media in Spain and was mainly directed at young people.